ETNOBOTANI TUMBUHAN BINAHONG (Anredera cordifolia) SEBAGAI OBAT SKABIES DI DESA CIPEUNDEUY, KECAMATAN BANTARUJEG, KABUPATEN MAJALENGKA - Wilma Mulyana, Fani; Cahyanto, Tri (Jurnal Nusa Sylva, 2023)
The high potential of the binahong (Anredera cordifolia) plant as a traditional medicine used by the people of Cipeundeuy Village is local wisdom that must be preserved so that it continues to be maintained as time goes by, so this research was carried out as knowledge about the use of binahong, especially for scabies, so that it can be more widely known. This research aims to analyze the use of the binahong plant as a traditional scabies medicine and its processing techniques. This research method is purposive sampling with data collection techniques, namely semi-structured interviews with 15 respondents consisting of two key informants and 13 members of the general public, then continued with exploration by seeing the processing process directly and documenting it. The results of the research show that 100% of the people of Cipeundeuy Village believe and practice using binahong leaves to treat skin disease, namely scabies, which causes wounds and itching. As many as 39% of people use the binahong plant by holding it in a bracelet (twisting it between the palms of their hands) and then rubbing it on, 33% drink it and 28% use it in the bath. The part of the plant used is the leaves which must be an odd number, usually 3.5 or 7 leaves. The ethanol content and chemical compounds in the form of flavonoids, tannins, saponins and triterpenoids are known to be healing agents for scabies caused by Sarcoptes scabiei mites and Staphylococcus aureus bacteria that live on the human epidermis.